Comparison of three device generations of the StepWatch Activity Monitor: analysis of model version agreement in pediatric and adult independent ambulators - Stevens, Wilshaw R.; Barrett, Cody; Jeans, Kelly A. (Frontiers in Sports and Active Living, 2024)
Devices like the StepWatch Activity Monitor have been available for 20 years and have been shown to accurately measure ambulatory activity. The purpose of this study was to evaluate the agreement among three generations of the StepWatch Activity Monitor (SW3, SW4, SW5) with respect to stride count. Methods Participants (n=36; age range 6-55 years) gave consent to participate in this institutional review board approved study. Participants were fitted with three different SAM model devices worn concurrently on the same leg. Participants performed a six-minute walk test (6MWT) and for the first two minutes of the test (2MWT), research staff manually counted the number of strides. Agreement among the device models was evaluated by calculating ANOVAs, ICCs and creating Bland-Altman plots.There was no significant difference among the model versions during the 6MWT or 2MWT (p>0.05). The ICC for total stride count during the 2MWT was 0.993 (95% C.I. = 0.988 -0.996) and 0.992 (95% C.I. = 0.986 -0.996) during the 6MWT. There was near perfect agreement (ICC≥0.990) of each model version to manually counted strides during the 2MWT. Systematic bias of all three SAM model versions was less than 1 step.Results from the present study demonstrate that stride counts among all three devices are comparable and relative to the manual stride count, all three SAM model versions had an ICC greater than 0.90. Researchers can safely incorporate historical data from previous SAM model versions with newer data collected with the latest SAM model.